PREVALENSI INFEKSI CACING PADA MURID SEKOLAH DASAR NEGERI 1 HARAPAN MAJU KECAMATAN KARANG BINTANG KABUPATEN TANAH BUMBU - Juhairiyah j; Budi Hairani; Liestiana Indriyati (SPIRAKEL, 2017)
One of worm infection is intestinal worms infection that are transmitted through the ground or often called Soil Transmitted helminths (STH). Soil Transmitted Helminth can infest humans of all ages , especially in children . This study aimed to examine the prevalence of worm infections in school children in Tanah Bumbu with cross sectional design . Research subjects are all students of class grade I - VI SDN 1 Harapan Maju Karang Bintang, Tanah Bumbu District. Result showed the prevalence of worm infection 16 %, which mostly occurs in girls (8.8 %) and in the group of age 9-11 years (6.8 %). Types of worms that infected the children are Trichuris trichiura, Ascaris lumbricoides, Enterobius vermicularis and Hookworm . The highest infection caused by T. trichiura (8.8 %). Beside single infection, mixed infections was also found, indicating the possibility of poor personal and environmental sanitation level around the child.